2016
DOI: 10.5653/cerm.2016.43.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes following the administration of high doses of dexamethasone in early pregnancy

Abstract: ObjectiveIn the present study, we aimed to evaluate the effects of high doses of dexamethasone (DEX) in early pregnancy on pregnancy outcomes.MethodsPregnant BALB/c mice were treated with high-dose DEX in the experimental group or saline in the control group on gestational days (GDs) 0.5 to 4.5. Pregnant mice were sacrificed on GDs 7.5, 13.5, or 18.5 and their peripheral blood, placentas, fetuses, and uterine tissue were collected. Decidual and placenta cell supernatants were examined to evaluate the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 49 publications
4
7
1
Order By: Relevance
“…The decreased progesterone concentration observed in this study is similar to that reported by Ahmadabad et al [ 43 ] in pregnant mice treated with dexamethasone, but Gale [ 44 ] and Ohrlander et al [ 45 ] who worked with dexamethasone to induce foetal lung maturation in human did not observe any alteration in the plasma concentrations of progesterone. In the present study, dexamethasone treatment did not alter circulating estrogen level during pregnancy in the Yankasa sheep although Ohrlander et al [ 45 ] previously reported suppression of estrogen production in pregnant women by dexamethasone.…”
Section: Discussionsupporting
confidence: 91%
“…The decreased progesterone concentration observed in this study is similar to that reported by Ahmadabad et al [ 43 ] in pregnant mice treated with dexamethasone, but Gale [ 44 ] and Ohrlander et al [ 45 ] who worked with dexamethasone to induce foetal lung maturation in human did not observe any alteration in the plasma concentrations of progesterone. In the present study, dexamethasone treatment did not alter circulating estrogen level during pregnancy in the Yankasa sheep although Ohrlander et al [ 45 ] previously reported suppression of estrogen production in pregnant women by dexamethasone.…”
Section: Discussionsupporting
confidence: 91%
“…Positive live birth outcomes in unexplained infertility and idiopathic recurrent miscarriage were obtained with low (or medium) dose of dexamethasone, prednisolone or prednisone, yet with low evidence level [ 67 , 132 , 134 , 135 ]. Nevertheless, many adverse maternal and fetal effects were reported in the studies where corticosteroids were administered at high doses [ 45 , 136 ]. Moreover, other molecules need to be assessed such as non-steroid-anti-inflammatory drugs (NSAIDs), whose prolonged prescription could oppose to follicle rupture though [ 137 ].…”
Section: Iise Assessment and Management: Future Perspectivesmentioning
confidence: 99%
“…Estradiol and progesterone levels were not significantly different in all groups. However, Ahmadabad et al (2016) had earlier reported a decrease in progesterone levels in pregnant mice treated with dexamethasone. Supplementation with Dialium guineense fruit pulp increased both LH, FSH and testosterone levels when compared to the pregnant control group.…”
Section: Discussionmentioning
confidence: 93%